Comparative Study of Farming Income from Large Chilies and Curly Chilies In Sheet District, West Lombok Regency - Yusmiati, Yusmiati; Anwar, Khairil; Rengganis, Baiq Santi (Implikasi: Jurnal Manajemen Sumber Daya Manusia, 2024)
One of the agricultural commodities that has high production potential is chili plants, chili is a type of agricultural commodity that has economic value and plays an important role in meeting the needs of the community. In West Lombok Regency, especially in East Mareje Village, Selamat District, the chili plants that are widely cultivated are large chili plants and chili pepper plants (Capsicum annum L). The two types of chili plants have price differences and high price fluctuations, due to differences in the use and availability of production of the two types of chili plants in the market. Therefore, research has been conducted which aims to determine the amount of income of large chili and chili farms, whether the income of large chili farms is higher than the income of chili farms, and whether the obstacles faced in the cultivation of large chili and chili peppers. In this study, the research methods and techniques used are comparative methods and direct interview techniques based on a list of questions that have been provided. The sample of respondent farmers was taken using the proportional random sampling method, where 30 people were taken from the large chili plant farms and 30 people were taken from the curly chili farms so that the number of respondents was 60 people. The results showed that the average income of large chili farms was IDR 5,309,000/LG or IDR 97,135,044/Ha, while the average income of curly chili farms was IDR 3,566,000/LG or IDR 70,542,331/Ha. The t-test results show that the equal variances are assumedobtained sign value. 0.00 is smaller than the significance value of the hypothesis test (0.05). This shows that Ho is rejected or H1 is accepted, which means that the average income of large chili farms is higher than curly chili.